PERAN BADAN NARKOTIKA NASIONAL KABUPATEN/KOTA (BNNK) DALAM PENCEGAHAN DAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOTIKA (P4GN) BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 DI KABUPATEN POLEWALI MANDAR - Azriel Pualillin; Desi Amalia Anwar; Patly Parakkasi (Jurnal Hukum Unsulbar, 2025)
This study examines the Role of the National Narcotics Agency of the City and Regency (BNNK) in the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) based on Law Number 35 of 2009 concerning Narcotics in Polewali Mandar Regency. This study aims to determine the role of BNNK and also the obstacles faced by BNNK in carrying out its duties related to the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) in Polewali Mandar Regency. The type of research used by researchers in researching is empirical (sociological) called a legal study in action (law in action) is called so, because the research concerns the reciprocal relationship between law and other social institutions, so it is a non-doctrinal social study, empirical in nature, meaning based on data that occurs in the field. The data obtained, both from field studies and literature studies are basically level data that are analyzed using normative analysis, namely the collected data is presented in the form of logical and systematic descriptions, then analyzed to obtain clarity in solving the problem, then conclusions are drawn deductively, namely from general things to specific things. The results of this study concluded that the Role of the Regency/City National Narcotics Agency (BNNK) in the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) in Polewali Mandar Based on the Regulation of the Head of the National Narcotics Agency Number 06 of 2020 concerning the Organization and Work Procedures of BNNP and BNNK/City. The Polewali Mandar Regency/City National Narcotics Agency (BNNK) carries out the duties, functions and authorities of the National Narcotics Agency (BNN) in the Polewali Mandar Regency/City area which are adjusted to the socio-cultural conditions of the Polewali Mandar community. Supporting factors for the role include the budget from the state budget (APBN), 31 personnel of the National Narcotics Agency of the Regency/City (BNNK), availability of office buildings, 1 Tipalayo Pratama Clinic room, 1 detention room, 5 motorbikes and 1 operational car unit. The obstacles faced by the National Narcotics Agency of the Regency/City (BNNK) in carrying out its duties related to the Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN); Limited budget availability, operational vehicles of the National Narcotics Agency of the Regency/City (BNNK) of Polewali Mandar are only 1 car and 5 motorbikes which limit operational activities, especially those requiring massive mobility, the number of human resources of the National Narcotics Agency of the Regency/City (BNNK) is not yet ideal, infrastructure in the form of the National Narcotics Agency office of the Regency/City (BNNK) of Polewali Mandar is still on loan, and there is no Narcotics laboratory in Polewali Mandar.